(untitled) (Bangladesh Journal of Microbiology, 2020)
Different types of diseases inflict the inhabitants of Dhaka city from time to time. The focus of this study was to investigate disease prevalence, etiology and antibiotic sensitivity profiles reported at a local diagnostic service in Dhaka, Bangladesh. Pathogens were transported from a renowned local diagnostic centre in Dhaka city in Trypticase Soy broth (TSB) to the laboratory. Antibiogram was performed by Kirby Bauer disc diffusion assay. A total of 110 samples (20% blood (n = 22), 60.9% urine (n = 67), 13.64% pus (n =15), 3.64% sputum (n = 4) and 1.82% wound swab samples (n = 2) were collected for further investigation. Of the patients, 30% were male and 70% were female. In case of blood samples from diarrheal patients, Salmonella enterica serovar Typhi (72.7%) and S. enterica serovars Paratyphi (27.2%) were predominant. Both serovars were sensitive to Cefixime, Ceftriaxone and Gentamicin and resistant to Nalidixic acid. E. coli (91%) was the predominant pathogen in Urinary Tract Infection (UTI) patients followed by Klebsiella spp. (8.9%). E. coli exhibited resistance to Cephalosporins and Ciprofloxacin whereas Klebsiella spp. were, however, sensitive to these antibiotics. Both species showed resistance against Amoxicillin and sensitivity to Imipenem, Merpenem and Colistin. In pus samples, S. aureus (46.7%) prevailed followed by Klebsiella spp. (26.7%) and E. coli (26.7%) spp. All S. aureus isolates were sensitive to Fusidic acid, Vancomycin, Linezolid and Piperacillin and 50% were sensitive to Cephalosporins and Ciprofloxacin and resistant to Amoxycillin and Azithromycin. E. coli and Klebsiella spp. from pus samples could be inhibited by Carbapenem. As with UTI isolates, E. coli from pus were resistant to Cephalosporins, Ciprofloxacin and Amoxicillin whereas 66% Klebsiella spp. were sensitive to the first two. A total of 66% of E. coli and Klebsiella spp. showed sensitivity to Gentamicin and Amikacin. It was observed that there was a similarity in the antibiotic sensitivity pattern of the same bacterial spp. isolated from different disease cases. As a general rule, it was observed that Imipenem is a good treatment option for treating E. coli and Klebsiella spp., Cephalosporins for Salmonella while a number of treatment options existed for S. aureus infections. Bangladesh J Microbiol, Volume 36 Number 2 December 2019, pp 99-104